2016
DOI: 10.1080/19420862.2015.1136762
|View full text |Cite
|
Sign up to set email alerts
|

Cross-arm binding efficiency of an EGFR x c-Met bispecific antibody

Abstract: Multispecific proteins, such as bispecific antibodies (BsAbs), that bind to two different ligands are becoming increasingly important therapeutic agents. Such BsAbs can exhibit markedly increased target binding and target residence time when both pharmacophores bind simultaneously to their targets. The cross-arm binding efficiency (x) describes an increase in apparent affinity when a BsAb binds to the second target or receptor (R2) following its binding to the first target or receptor (R1) on the same cell. x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 45 publications
(58 reference statements)
3
23
0
Order By: Relevance
“…S4), the affinity-reduced variants displayed lower EC 50 values upon binding to the double-positive NCI-H358 cells compared with EC 50 values obtained for the single-positive HER2 knock out cells. Our results are in agreement with recent reports, demonstrating that, depending on the spatial arrangement of the antigen binding sites as well as the antigen surface distribution and density, significant functional avidity may be triggered by cross-arm binding14162030. Remarkably, a 10-fold reduction in affinity of the EGFR arm was not sufficient to significantly enhance target selectivity over that obtained with the parental DuetMab, as evidenced by a mean TSP value of 0.07 acquired for variant VκF94A.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S4), the affinity-reduced variants displayed lower EC 50 values upon binding to the double-positive NCI-H358 cells compared with EC 50 values obtained for the single-positive HER2 knock out cells. Our results are in agreement with recent reports, demonstrating that, depending on the spatial arrangement of the antigen binding sites as well as the antigen surface distribution and density, significant functional avidity may be triggered by cross-arm binding14162030. Remarkably, a 10-fold reduction in affinity of the EGFR arm was not sufficient to significantly enhance target selectivity over that obtained with the parental DuetMab, as evidenced by a mean TSP value of 0.07 acquired for variant VκF94A.…”
Section: Resultssupporting
confidence: 91%
“…Bispecific antibodies (bsAb) by virtue of simultaneously targeting two disease mediators offer greater therapeutic efficacy as well as the capacity to overcome major escape mechanisms evident in mono-targeted therapy9101112. The underlying perception is that dual targeting of antigen double-positive cells over single-positive normal tissues leads to improved target selectivity owing to a strong avidity effect mediated by concurrent binding of the bsAb to both antigens on the surface of the same cell1314151617. It is therefore believed that these new bio-therapeutic agents will open a new era of targeted therapy, providing attractive opportunities of enhanced efficacy coupled with reduced systemic toxicity, leading to an overall improved therapeutic index (TI).…”
mentioning
confidence: 99%
“…We have described correlations between binding affinity, receptor density, and receptor phosphorylation with JNJ-61186372 (19). Furthermore, we have shown that JNJ-61186372 was more effective than the combination therapy of anti-EGFR and anti-cMet monovalent antibodies in decreasing tumor growth in the H1975-HGF model (31).…”
Section: Discussionmentioning
confidence: 94%
“…56,57 The monovalent binding nature of this class of molecules is believed to promote improved target selectivity via cross-arm avidity targeting of antigen double-positive cells over single-positive normal tissue. [58][59][60][61] This feature is of substantial importance because it provides attractive opportunities of enhanced efficacy coupled with reduced systemic toxicity that can potentially lead to better drug safety and improved therapeutic index. However, with respect to the ability of monovalent bispecific antibodies to mediate Fc-dependent immune effector functions as a mode of action, the findings we presented here, combined with data we recently reported in relation to the effect of antibody binding valency on the capacity to regulate ADCC, may suggest that monovalent binding of a bispecific antibody to a cell surface antigen on single-positive normal tissue may correspond with substantial augmentation of immune effector functions and potential damaging of nontarget cells.…”
Section: Discussionmentioning
confidence: 99%